Current Status of Schistosomiasis Control and Prospects for Elimination in the Dongting Lake Region of the People’s Republic of China - Li, Fei-Yue; Hou, Xun-Ya; Tan, Hong-Zhuan; Williams, Gail M.; Gray, Darren J.; Gordon, Catherine A.; Kurscheid, Johanna; Clements, Archie C. A.; Li, Yue-Sheng; McManus, Donald P. (Frontiers in Immunology, 2020)
Abstract：Schistosomiasis japonica is an ancient parasitic disease that has severely impacted human health causing a substantial disease burden not only to the Chinese people but also residents of other countries such as the Philippines, Indonesia and, before 1970s, Japan. Since the founding of the new People's Republic of China (P. R. China), effective control strategies have been implemented with the result that the prevalence of schistosomiasis japonica has decreased dramatically in the past 70 years.Historically, the Dongting Lake region in Hunan province is recognised as one of the most highly endemic for schistosomiasis in the P.R. China. The area is characterised by vast marshlands outside the lake embankments and, until recently, the presence of large numbers of domestic animals such as bovines, goats and sheep that can act as reservoir hosts for Schistosoma japonicum (S. japonicum). Considerable social, economic and environmental changes have expanded the Oncomelania hupensis hupensis (O.h. hupensis) intermediate snail host areas in the Dongting lake region increasing 2 the potential for both the emergence of new hot spots for schistosomiasis transmission, and for its re-emergence in areas where infection is currently under control. In this paper, we review the history and the current endemic status of schistosomiasis and the control strategies in operation in the Dongting Lake region. We also explore epidemiological factors contributing to S. japonicum transmission and highlight key research findings from studies undertaken on schistosomiasis mainly in Hunan but also other endemic Chinese provinces over the past 10 years. We also consider the impact of these research outcomes on current and future approaches that can lead to the sustainable integrated control and final elimination of schistosomiasis from the P. R.China and other countries in the region where this unyielding disease persists.